Delayed laparoscopic repair of a traumatic flank hernia: A case report and review of the literature. (2018) - Ferris, Mead; Pirko, Christopher; Nottingham, James
Highlights: Not all traumatic abdominal wall hernias require laparotomy at time of injury. Observation is considered to be safe when there is no other indication for surgery. Many patients managed non-operatively remain asymptomatic. Delayed laparoscopic repair with mesh reserved for hernias that become symptomatic. Abstract: Introduction: The traumatic abdominal wall hernia is a rare injury typically due to a high-energy blunt trauma mechanism. There is a lack of consensus on the appropriate management of these patients. Presentation of the case: A 43-year-old male was evaluated for a left flank bulge eight months after a motorcycle collision. He was diagnosed with a traumatic abdominal wall hernia at time of injury that was managed non-operatively. He noticed a left flank bulge two months after his collision that progressively worsened in size and in discomfort. The patient underwent laparoscopic repair of the traumatic flank hernia. His postoperative course was uneventful and there was no recurrence at 3 years. Discussion: Historically, exploratory laparotomy was considered necessary in patients diagnosed with a traumatic abdominal wall hernia at time of injury due to the high-percentage of concomitant intra-abdominal injuries. More recent studies suggest that some patients with a traumatic abdominal wall hernia may be safely managed non-operatively. A minority of these patients will require surgery for symptoms or complications related to the hernia and laparoscopic repair performed in a delayed fashion appears to have improved outcomes when compared to those that undergo repair at time of injury. Conclusion: There is growing evidence supporting a non-operative management strategy in patients with a traumatic abdominal wall hernia who do not have a clear indication for abdominal surgery. These patients may be safely observed with delayed laparoscopic repair using synthetic mesh reserved for traumatic abdominal wall hernias that become symptomatic.